2002
DOI: 10.1063/1.1449864
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous dimethyl sulfoxide solutions: Inter- and intra-molecular dynamics

Abstract: The inter- and intra-molecular dynamics of aqueous dimethyl sulfoxide (DMSO) solutions have been measured using optical heterodyne-detected Raman-induced Kerr effect spectroscopy. Solutions were studied over the entire range of composition at 294 K. The Kerr transients characterize both the underdamped inter- and intra-molecular vibrational motions, as well as the overdamped, diffusive orientational motions. The longer diffusive relaxation time constant τ2 is assigned to DMSO reorientation, and varies strongly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
83
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 65 publications
10
83
0
Order By: Relevance
“…In the DMSO molecule, the partial positive and negative charges on sulphur and oxygen atoms, respectively, give rise to the large dipole moment (4.1 D, gas phase [19]). The length of the S=O bond for free molecule was 1.495 Å [20], while in our measurements the length is found to be longer (1.552(12) Å ) due to the H-bond formation with the betulin molecule (see Fig.…”
Section: X-ray Crystal Structurementioning
confidence: 99%
“…In the DMSO molecule, the partial positive and negative charges on sulphur and oxygen atoms, respectively, give rise to the large dipole moment (4.1 D, gas phase [19]). The length of the S=O bond for free molecule was 1.495 Å [20], while in our measurements the length is found to be longer (1.552(12) Å ) due to the H-bond formation with the betulin molecule (see Fig.…”
Section: X-ray Crystal Structurementioning
confidence: 99%
“…[10] At this mixing ratio a viscosity maximum is reached and an extended reordering process takes place, [10] thus leading to different diffusion dynamics, hindered rotation, and the absence of stable HBs between DMSO and water. [11][12][13] Along with the mentioned nonideal mixing behavior, a local heterogeneity of DMSO/ water mixtures has been discovered by both experimental techniques [14] and molecular dynamics simulation methods. [15][16][17] Aside from the molecular formations of DMSO molecules, the origin of inter-and intramolecular interactions leadThe effects of hydrogen bonding between dimethyl sulfoxide (DMSO) and the co-solvents water, methanol, and ethanol on the symmetric and antisymmetric CSC stretching vibrations of DMSO are investigated by means of Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 97%
“…Accordingly, the diffusive orientational relaxation for a spherical molecule is forbidden, and the isotropic vibrational modes are silent for this spectroscopic condition. It is also possible to detect the isotropic vibrational modes by changing the polarization angles for the spectroscopic setup (Khalil et al, 2000;Wiewior et al, 2002;Heisler & Meech, 2010). Line-shape analysis is also carried out to characterize the Kerr spectra.…”
Section: Femtosecond Raman-induced Kerr Effect Spectroscopy: Principlmentioning
confidence: 99%
“…As mentioned above, femtosecond RIKES has also been used to investigate ILs . The details of the femtosecond RIKES setups used for the studies described in this chapter have been reported elsewhere (Wiewior et al, 2002;Shirota, 2005;. In short, the light sources for the setups were titanium:sapphire lasers pumped by approximately 3.5 W of 532-nm light from a neodymium:vanadate laser (Spectra Physics).…”
Section: Femtosecond Raman-induced Kerr Effect Spectroscopy: Principlmentioning
confidence: 99%